DEMONSTRATION OF GENDER IN CHILDREN FANTASY FICTION: A SEMIOLOGICAL DISCOURSE ANALYSIS(SDA) OF PRIMARY SCHOOL STORY BOOKS - Tahira shabbir; Rukhshinda Jabeen; Dr. Mahwish Farooq (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
This study concentrates on children's fantasy fiction to investigate gender representations in a selection of elementary school storybooks. This study reveals gender ideology in terms of how gender stereotypes are represented via linguistic and semiotic means. Children's literature influences gender ideology. When students read stories with stereotypically portrayed characters, they reinforce preconceived notions. Stories are constructed in cultural context. Children are products of this particular cultural context, and they tend to conduct in accordance with the gendered ideologies ingrained in cultural discourse. Fantasy novels are historical records. The current qualitative study concentrates on children's literature to examine gender representations. The research examines fifteen works of children's fantasy fiction. The data was collected using the technique of systematic sampling. For the Critical Discourse Analysis of narratives, a qualitative approach has been employed, and the frameworks of Fairclough (1995), Barthes (1974), and Kruger (2000) have been utilised for critical and semi-logical analysis. The findings indicate that 21st-century children's fantasy literature emphasises gender representations. In patriarchal societies, males are dominant, as has been observed. Because they have power, they are free to exercise their free will in every situation, whereas women are valued for domestic purposes. In some legends, women have been portrayed as demons, while men have been depicted as dependent on women. The study also reveals the role of customs and traditions in determining the destinies of women. Through the analysis of picture books, this study expands our understanding of the phenomenon of gender representations and encourages future scholars to conduct additional academic research on gender representations in other pedagogical sources, such as novels, dramas, morning shows, newspapers, magazines, and talk shows, etc.